2018
DOI: 10.1186/s41747-018-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy for hypersplenism with or without preoperative splenic artery embolisation

Abstract: BackgroundAlthough splenectomy is considered the preferred treatment for hypersplenism, intraoperative blood loss remains a common occurrence. We prospectively compared the perioperative and clinical outcome of splenic artery embolisation (SAE) before open splenectomy (OS) versus OS alone in two concurrent patient groups.MethodsFrom January 2016 to January 2018, 50 patients with hypersplenism underwent combined SAE and OS (study group). For comparison, we considered 50 age- and gender-matched case controls und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Prior literature has shown that SAE allows for easier intraoperative handling of the organ, decreased blood loss, a decrease in splenic weight before removal, and fewer postoperative blood transfusions. 4 However, the average spleen size in this study was 16.2 cm (SD 4 3.9). 4 In our patient, only 3 units of packed red blood cells were used during his hospital stay.…”
Section: Hybrid Surgical Management For Massive Splenomegaly In a Sepmentioning
confidence: 55%
See 1 more Smart Citation
“…Prior literature has shown that SAE allows for easier intraoperative handling of the organ, decreased blood loss, a decrease in splenic weight before removal, and fewer postoperative blood transfusions. 4 However, the average spleen size in this study was 16.2 cm (SD 4 3.9). 4 In our patient, only 3 units of packed red blood cells were used during his hospital stay.…”
Section: Hybrid Surgical Management For Massive Splenomegaly In a Sepmentioning
confidence: 55%
“…4 However, the average spleen size in this study was 16.2 cm (SD 4 3.9). 4 In our patient, only 3 units of packed red blood cells were used during his hospital stay. He was discharged home after 14 days in the hospital.…”
Section: Hybrid Surgical Management For Massive Splenomegaly In a Sepmentioning
confidence: 55%
“…Portal hypertension-induced hypersplenism causes thrombocytopenia [41]. Splenectomy can effectively reduce portal pressure and correct hypersplenism and improve hypersplenism-induced thrombocytopenia [42, 43]. In this study, patients' portal vein pressure was significantly decreased after splenectomy.…”
Section: Discussionmentioning
confidence: 74%
“…Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time 15,16 . Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed 17–19 . Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8‐week interval is recommended prior to postoperative vaccination of the patient 20 …”
Section: Discussionmentioning
confidence: 99%
“…15,16 Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed. [17][18][19] Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8-week interval is recommended prior to postoperative vaccination of the patient. 20 Prior research suggests that patients can have a sustained response to either medical therapy or splenectomy, though studies suggest a higher percentage of surgical patients have a sustained response compared to patients who receive medical therapy for ITP.…”
Section: Discussionmentioning
confidence: 99%